The Implementation of Extracurricular Tahfidz Al-Quran to Increase Student Achievement at MTsN 3 Tulungagung - Fauziah, Kuni Isna Ariesta; Achadi, Muh. Wasith (The Pontianak State Institute of Islamic Studies, 2020)
Al-Quran is the greatest miracle of Muslims completing the previous book that must be studied. Tahfidz Al-Quran is present in various boarding schools, formal schools, non-formal schools, to the special institutions of Tahfidz Al-Quran. Starting with applying the results of research at the Hanifida Al-Quran Islamic Boarding School, Jombang in a special class, the extracurricular tahfidz Al-Quran was formed for the regular class as a forum for the talents and interests of students. As well as actualizing the vision and mission of the madrasa in religious terms. Research focus: discussing the existence of tahfidz Al-Quran extracurricular activities aimed at: (1) knowing the form of implementation of Al-Quran tahfidz extracurricular activities (2) knowing the achievements of extracurricular tahfidz al-Quran in MTsN 3 Tulungagung. The research method uses a descriptive qualitative approach. With the technique of collecting interviews, observation, and documentation. Through data analysis techniques: data reduction, data presentation, and drawing conclusions. Data validity checking: method and source triangulation test. The results of the research: (1) program or extracurricular form of tahfidz Al-Quran at MTsN 3 Tulungagung, among others: a) deposits, b) guidance, c) deresan, d) evaluation (continued verse), and e) pesantren kilat (2) The achievements given by extracurricular tahfidz Al-Quran students at MTsN 3 Tulungagung include: a) in the academic field and b) non-academic.